2015
DOI: 10.1039/c5cp00132c
|View full text |Cite
|
Sign up to set email alerts
|

Influence of H- and OH-adsorbates on the ethanol oxidation reaction – a DEMS study

Abstract: The ethanol oxidation reaction (EOR) was investigated by potentiodynamic techniques on Pt/C, Rh/C, Pt-Rh/C, Pt-SnO2/C and Pt-Rh-SnO2/C by differential electrochemical mass spectrometry (DEMS) in a flow cell system. Prior to the cyclic voltammetries, adsorption of H- and OH-species was carried out by chronoamperometry at Ead = 0.05 and 1 V vs. RHE, respectively, in order to examine their influence on the EOR on the different electrocatalysts. For the sake of comparison, another adsorption potential was chosen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 64 publications
(110 reference statements)
2
24
0
Order By: Relevance
“…Thus, the Rh @ Pt 5.3L NW/C catalysts presented the highest capacity for producing acetic acid but poor selectivity toward CO 2 . It has been demonstrated that the CO 2 current efficiency (a quantification of the current generated form the CO 2 pathway reported to the EOR overall current) is generally found to be only between 5 and 20% . The overall activity for EOR should integrate both the CO 2 and CH 3 CH 2 OH pathways into account.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the Rh @ Pt 5.3L NW/C catalysts presented the highest capacity for producing acetic acid but poor selectivity toward CO 2 . It has been demonstrated that the CO 2 current efficiency (a quantification of the current generated form the CO 2 pathway reported to the EOR overall current) is generally found to be only between 5 and 20% . The overall activity for EOR should integrate both the CO 2 and CH 3 CH 2 OH pathways into account.…”
Section: Resultsmentioning
confidence: 99%
“…The calibration of the m/z = 22 mass-to-charge signal was carried out according to the protocol detailed in ref. 23…”
Section: Calibration Of the Mass Spectrometermentioning
confidence: 99%
“…In spite of the performance increase observed in DEFCs currently operating at temperatures between 80-120 °C, the selectivity towards CO2 of most of these materials still remains low [39]. The most promising are the PtRh/C-based catalysts, which show an increase in the current density for the ethanol oxidation and an enhancement in the CO2 yield under mild operating conditions (T ≤ 90 °C) [40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%